INTERAKSI ANTARA KOMUNIKASI DAN PENGAWASAN TERHADAP MOTIVASI KERJA APARATUR SIPIL NEGARA (ASN) - Fadhilah, Fadhilah; Rusham, Rusham; Pramono, Joko (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
Research on communication and supervision on employee performance results are still mixed. These mixed results may be because the study did not pay attention to the condition of the organizational structure of the organization studied. This study uses three hypotheses, the influence of communication on motivation, the influence of supervision on motivation, and the influence of interaction between communication and supervision on employee work motivation. The design of this study is quantitative research with multiple regression analysis. The research location is in Bappeda Bekasi City. The results of this study stated that communication and supervision each had a significant positive effect on motivation, while the interaction between communication and supervision had a significant negative effect. The results of this study can be concluded that in the environment of Bappeda employees what is needed is effective communication and supervision. From the results of this study, it is recommended to develop the effectiveness of this supervision and communication, and for other researchers, it is recommended to confirm in other locations by paying attention to the organizational structure.